A Reverse Logistics Model for Optimization in Waste Collection - Prasad, Sahana (Prabandhan: Indian Journal of Management, 2015)
Sustainability has become a major concern in the development of human society. This requires solution of certain issues and involves social, technical, legislative, and other factors. An important concern is to minimize the generation of wastes, prevent environmental deterioration caused by the generation of wastes, and to enhance the value of recovery from the wastes. The reverse logistics network is helpful in this regard as its mission is to collect and transport used products and packages based on the balance of cost and environment. A good reverse logistics network is important for firms to gain more profits. This paper proposed a linear programming model for reverse logistics in which collection is done when the recyclables bin is half full. This limit can be varied from place to place, depending on the collection of recyclables. The model aimed to reduce transportation cost by setting up a schedule for collection and took into account the profit obtained by recycling. It also considered a penalty for late collection so that there is no piling up of waste, thus reducing the probability of items deteriorating due to weather or moisture content.